Water Footprint Assessment pada Komoditas Padi, Jagung, dan Kedelai di Wilayah Daerah Istimewa Yogyakarta untuk Mendukung Sistem Pertanian Berkelanjutan - Fathi Alfinur Rizqi; Sri Nuryani Utami (Jurnal Irigasi, 2020)
Indonesia's population is estimated to reach 350 million by 2045, encouraging Indonesia to increase food availability by 3% every year. The Upsus Pajale (Upaya Khusus Padi Jagung Kedelai) program is one of the government's flagship programs in responding to this challenge. On the other hand, environmental pressures provide clear boundaries for implementing a sustainable agricultural process. As the two goals of the Sustainability Development Goals (SDGs) are to zero hunger and ensure access to water, concept of virtual water is present as an alternative concept along with a water counting tool needed in an agricultural production process. This research was conducted to assess water footprint for rice, corn, and soybean in the Special Region of Yogyakarta. The analysis resulted in the term water footprint assessment consist of blue water, green water, and grey water. The results showed that the annual water footprint of soybean was the highest at 2,589 m3/ton, followed by field rice, corn, and lowland rice at 1,280 m3/ton; 844 m3/ton; 841 m3/ton. The results are due to higher level of productivity resulting lower of the water footprint. The implementation of this research reveals the factors that influence the amount of water needed (Virtual Water) to produce agricultural commodities. Whereas location selection, climatic conditions, types of plants, cultivation techniques, and the use of fertilizers are factors that need to be considered to reduce water use in the agriculture production processes. Thus, the objectives of implementing sustainable agricultural cultivation can be realized.